Crystal Structure Elucidation and Anticancer Studies of (-)-Pseudosemiglabrin: A Flavanone Isolated from the Aerial Parts of Tephrosia apollinea - Ahmed Hassan, Loiy Elsir; Khadeer Ahamed, Mohamed B.; Abdul Majid, Aman Shah; Iqbal, Muhammad Adnan; Al Suede, Fouad Saleih R.; Haque, Rosenani A.; Ismail, Zhari; Ein, Oon Chern; Majid, Amin Malik Shah Abdul (PLOS ONE, 2014)
Tephrosia apollinea is a perennial shrublet widely distributed in Africa and is known to have medicinal properties. The current study describes the bio-assay (cytotoxicity) guided isolation of (-)-pseudosemiglabrin from the aerial parts of T. apollinea. The structural and stereochemical features have been described using spectral and x-ray crystallographic techniques. The cytotoxicity of isolated compound was evaluated against nine cancer cell lines. In addition, human fibroblast was used as a model cell line for normal cells. The results showed that (-)-pseudosemiglabrin exhibited dose-dependent antiproliferative effect on most of the tested cancer cell lines. Selectively, the compound showed significant inhibitory effect on the proliferation of leukemia, prostate and breast cancer cell lines. Further studies revealed that, the compound exhibited proapoptotic phenomenon of cytotoxicity. Interestingly, the compound did not display toxicity against the normal human fibroblast. It can be concluded that (-)-pseudosemiglabrin is worthy for further investigation as a potential chemotherapeutic agent.